Recurrent acute liver failure due to NBAS deficiency: phenotypic spectrum, disease mechanisms, and therapeutic concepts - Staufner, Christian; Straub, Beate Katharina; Kölker, Stefan; Thiel, Christian; Dikow, Nicola; Harting, Inga; Beisse, Flemming; Burgard, Peter; Kotzaeridou, Urania; Lenz, Dominic; Hoffmann, Georg F. (Journal of inherited metabolic disease, 2016)
Background Acute liver failure (ALF) in infancy and childhood is a life-threatening emergency and in about 50 % the etiology remains unknown. Recently biallelic mutations in NBAS were identified as a new molecular cause of ALF with onset in infancy, leading to recurrent acute liver failure (RALF). Methods The phenotype and medical history of 14 individuals with NBAS deficiency was studied in detail and functional studies were performed on patients’ fibroblasts. Results The phenotypic spectrum of NBAS deficiency ranges from isolated RALF to a multisystemic disease with short stature, skeletal dysplasia, immunological abnormalities, optic atrophy, and normal motor and cognitive development resembling SOPH syndrome. Liver crises are triggered by febrile infections; they become less frequent with age but are not restricted to childhood. Complete recovery is typical, but ALF crises can be fatal. Antipyretic therapy and induction of anabolism including glucose and parenteral lipids effectively ameliorates the course of liver crises. Patients’ fibroblasts showed an increased sensitivity to high temperature at protein and functional level and a disturbed tethering of vesicles, pointing at a defect of intracellular transport between the endoplasmic reticulum and Golgi. Conclusions Mutations in NBAS cause a complex disease with a wide clinical spectrum ranging from isolated RALF to a multisystemic phenotype. Thermal susceptibility of the syntaxin 18 complex is the basis of fever dependency of ALF episodes. NBAS deficiency is the first disease related to a primary defect of retrograde transport. Identification of NBAS deficiency allows optimized therapy of liver crises and even prevention of further episodes.
Published online: 5 November 2015
Gesehen am 13.05.2020